Zdolność do czynności prawnych a zdolność procesowa – na wybranych przykładach w sprawach z zakresu prawa osobowego i rodzinnego : [Contractual capacity vs. capacity to sue or be sued exemplified on cases of personal and family law] (Studia Prawnicze / The Legal Studies, 2011)
W nauce przyjmuje się, że zdolność procesowa jest odpowiednikiem zdolności do czynności prawnych, co oznacza że osoba fizyczna posiada zdolność procesową w takim zakresie, w jakim wyposażona jest w zdolność do czynności prawnych. Istnieją jednak osoby, które pomimo braku albo ograniczonej zdolności do czynności prawnych, mają zdolność procesową. Szczególne przypadki zdolności procesowej występują w - szeroko rozumianych - sprawach rodzinnych oraz w sprawach z zakresu prawa osobowego. Pod pojęcie spraw rodzinnych sensu largo mieścić się będą zarówno sprawy rozpoznawane w postępowaniu procesowym (w postępowaniu odrębnym w sprawach ze stosunku między rodzicami a dziećmi), jak i w postępowaniu nieprocesowym (sprawy z zakresu prawa rodzinnego, opiekuńczego i kurateli). In doctrine it is accepted that capacity to sue or be sued is a counterpart of contractual capacity, which means that a natural person has got capacity to sue or be sued in the same respect as it is equipped with contractual capacity. There are, however, persons who despite not having contractual capacity or having limited contractual capacity, have got capacity to sue or be sued. Establishing correlation between contractual capacity and capacity to sue or be sued requires considering the following: 1) whether the capacity to sue or be sued covers the contractual capacity or they are only interrelated, 2) whether it is possible to have capacity to sue or be sued without having contractual capacity, 3) whether a person not having contractual capacity or having it limited have the capacity to sue or be sued in civil proceedings and if it does whether it is full or limited. Presuming directly contractual capacity for capacity to sue or be sued is not in every respect correct. Since the Code of Civil Procedure does not designate persons having capacity to sue or be sued, it is necessary to refer in that respect to provisions of material law. The Code of Civil Procedure, however, gives exceptions to the rule according to which provisions of material law on contractual capacity prescribe the capacity to sue or be sued. However, some persons with limited contractual capacity (partially incapacitated or minors from articles 4531 and 573 of the Code of Civil Procedure) have full capacity to sue or be sued not only in cases deriving from legal activities that they are capable to perform but also in cases concerning their incapacitation as well as some cases of family and custody law. Exceptionally, it is possible for a person certified as being mentally unsound, thus a person without contractual capacity to perform procedural activities, but only in cases referring to its incapacitation (articles 559§3 and 560 of the Code of Civil Procedure). There is no express dependence between contractual capacity and capacity to sue or be sued. Therefore, capacity to sue or be sued cannot be said to be a counterpart of contractual capacity; nevertheless it can be said that they are strictly connected.